Creating a corporate entrepreneurial ecosystem: The case of entrepreneurship education in the rtp, USA - Jong-in Choi; Stephen K. Markham (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Today's dynamic and complex environment means that companies are trying to develop entrepreneurial thinking as a competitive advantage. Universities around the world are simultaneously increasing entrepreneurial training across a broad array of majors. However, the entrepreneurial training is not heavily connected to industry needs. This paper focuses on how industry and universities can cooperate to prepare students for corporate entrepreneurial thinking. The research is based on extensive literature, reports, and in-depth interviews with 28 people from various parts of the RTP (Research Triangle Park), including companies, government agencies, and numerous programs at multiple universities. The major finding from this study is that the strength of entrepreneurial education in the regional innovation system reinforces the companies' open innovation capacity and their performance. To be successful at launching campus-wide entrepreneurship education to increase understanding of corporate entrepreneurship, Corporate Entrepreneurship Education (CEE) must include (1) entrepreneurial leadership; (2) faculty champions; (3) student-focused policies; (4) engagement with the community; and (5) a decentralized, autonomous structure of entrepreneurship programs.
Keywords: 650; entrepreneurial ecosystem; entrepreneurship education; faculty champions; Research Triangle Park (RTP); triple helix model